Retroperitoneal Perforation of the Appendix Presenting as a Right Thigh Abscess. (1st March 2015) - Nanavati, Aditya J.; Nagral, Sanjay; Borle, Nitin
Abstract : A rare case of a retroperitoneal rupture of the appendix is being reported here. A 53-year-old male presented to us with a right sided thigh abscess. There were not any abdominal complaints at presentation. There was continuous discharge after incision and drainage from the thigh. Isolation, in culture, of an enteric bacterium from the pus prompted an evaluation of the gastrointestinal tract as a possible source. An MRI scan revealed fluid tracking from the right paracolic gutter over the psoas sheath and paraspinal muscle into the thigh. A CT scan revealed the perforation at the base of the appendix into the retroperitoneum. At laparotomy the above findings were confirmed. A segmental ileocaecal resection was done. The patient made an uneventful recovery. The absence of abdominal symptoms at presentation leads to delay in diagnosis in such cases. Nonresolving thigh and groin abscesses should lead to the evaluation of the gastrointestinal tract as origin. Diagnostic clues may also be provided by culture reports what as happened in this case.